2020
DOI: 10.1155/2020/8835813
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Beer Polyphenols and Their Bioavailability in Dental-Derived Stem Cells (D-dSCs) and Human Intestinal Epithelial Lines (Caco-2) Cells

Abstract: Beer is one of the most consumed alcoholic beverages in the world, rich in chemical compounds of natural origin with high nutritional and biological value. It is made up of water, barley malt, hops, and yeast. The main nutrients are carbohydrates, amino acids, minerals, vitamins, and other compounds such as polyphenols which are responsible for the many health benefits associated with this consumption of drinks. Hops and malt are one of the raw materials for beer and are a source of phenolic compounds. In fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…In the presence of an intense stressing event, cells activate specific responses to counteract cell death or senescence, which is known to act as a key task in the onset of age-related pathologies and the loss of tissue homeostasis [ 22 ]. Phenolics are generally recognized to be responsible for antioxidant and anti-aging effects, as well other beneficial actions [ 23 ]. Previous research showed that the total phenolic content of A. membranaceus from Western Siberia ranged from 100–190 mg GAE/g extract [ 24 ], which is consistent with this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of an intense stressing event, cells activate specific responses to counteract cell death or senescence, which is known to act as a key task in the onset of age-related pathologies and the loss of tissue homeostasis [ 22 ]. Phenolics are generally recognized to be responsible for antioxidant and anti-aging effects, as well other beneficial actions [ 23 ]. Previous research showed that the total phenolic content of A. membranaceus from Western Siberia ranged from 100–190 mg GAE/g extract [ 24 ], which is consistent with this study.…”
Section: Resultsmentioning
confidence: 99%
“…We now know with certainty how our lifestyle, and above all our eating habits, are able to produce profound changes in our intestinal flora, changing its composition, ecology and functionality [55]. There is increasing evidence that a diet rich in polyphenols-present mainly in foods and beverage of plant origin-can have an anti-oxidant and anti-obesity effect in humans [27,70]. A healthy and balanced diet, which also includes a correct daily consumption of calories-nowadays in the Western world a target to be pursued with difficulty-produces positive effects on our health, with different molecular mechanisms, some of which directly involve the microbiota [27].…”
Section: Dietary Interventions and Microbiota Modulationmentioning
confidence: 99%
“…BSG is a good source of valuable bioactive ingredients such as phenolic compounds extracted for the potential revalorization of this waste. The commercial usage of BSG bioactive extracts has already been explored as a nutraceutical ingredient, but its implementation in the cosmetic industry has only recently started to be proposed (Almendinger et al, 2020;Bucci et al, 2020;Di Domenico et al, 2020).…”
Section: Introductionmentioning
confidence: 99%